Analisis Praktik Kantor Akuntan Publik Di Indonesia Dalam Penyusunan Materialitas - Niken Ayu Sri Antoro (Jurnal Kewirausahaan Cerdas dan Digital, 2024)
This research aims to analyze the practices of Public Accounting Firms (KAP) in Indonesia in the process of preparing materiality. Materiality is an important concept in auditing that influences audit decisions and disseminates financial information. This research method involves surveys and data analysis from a number of KAPs operating in Indonesia. The results of this analysis provide in-depth insight into how KAPs in Indonesia view, identify and assess materiality in the audit context. The implications of these findings can provide guidance for practitioners and regulators in improving audit quality in Indonesia.